DYNAMICS OF INVESTMENT, POPULATION, AND EMPLOYMENT AND THEIR IMPACT ON ECONOMIC GROWTH IN SUMATRA ISLAND - Silvia Rahayu,; Dewi Ernita,; Muhammad Afdhal Chatra Perdana, (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
The research aims to find out whether investment, population and workforce have an effect on the economy, and how much influence investment, population and workforce have on the economy on the island of Sumatra. The data used is secondary data obtained from the official website of the Indonesian Central Statistics Agency (BPS). The data in this research was analyzed using qualitative descriptive analysis and quantitative descriptive analysis. The analysis tools used are multiple linear regression, hypothesis testing and the Coefficient of Determination (KD). On the day of the research, partial results showed that there was an influence between investment on the economy. This was proven by the results of t-count > t-table (-0.920 > -4.302), there was no influence between population and the economy. This was proven by the results of t- count < t-table (0.353 < 4.302), there is an influence between Labor and the Economy, this is proven by t-count > t-table (-1.723 > -4.302). Partially, the magnitude of the influence of Investment on the Economy is 71.57, Population on the Economy is 26.77 and Labor on the Economy is -14.62. The magnitude of the simultaneous influence is 83.2%. The remaining 100% - 83.2% = 16.8% is influenced by other variables not examined in this study.